Kajian kes mengenai penggunaan perisian sosial di perpustakaan IPTA dan IPTS di Malaysia - Mohd Zain, Faizah; Mahmood, Rohana; Mukandar, Anna Kustyana; Mohd Yusof, Mazni; Sukarno, Norliah; Mohamad Hamzah, Azlan; Abdollah, Kamaruddin; Badzri, Shaizimah; Ahmad Husaini, Norhamsiah; Kamis, Ruzita; Mohd Rohani, Rohalia; Isa, Mariatul Qibtiah; et al. (Persatuan Pustakawan Malaysia, 2009)
Web 2.0 is an application and social networking software that provides interactive information sharing, user oriented design and collaboration on the Internet. Some popular social software that are being used are Facebook Twitter, Blog dan Flickr. This article is the results of a study which seeks to identify the usage of Web 2.0 applications in 20 public and 14 private academic libraries throughout Malaysia. A virtual survey was conducted from October 2009 to February 2010. The findings show that Web 2.0 applications are being used in some academic libraries. Currently, the Blog is the most widehly used application.